Effect Of Magnesium Surfactant On Wettability Of Carbon Nanotube In A356 Alloy Composite - Salleh, Mohd Shukor; Hashim, Hanizam; Yahaya, Saifudin Hafiz; Nurhadi, Siswanto (Penerbit UTeM, 2019)
MWCNT-A356 alloy composite is a promising material for automotive applications owing to its excellent casting fluidity, good mechanical properties, high corrosion resistance and low density. However, wettability problem between the reinforced particles and alloy matrix is the major concerns. Poor wetting also caused inhomogeneity dispersion of the particles in the matrix. The present study investigated the effects of additional pure magnesium surfactant into the liquid state processing method on the mechanical properties of the composite. A thixoforming and short T6 heat treatment have also been applied to the composite. The composites were characterized using optical microscopy, field emission secondary electron microscopy and mechanical testing. As results, the weight fraction of 0.5 wt% of Mg, added into the 0.5 wt% MWCNT-A356 alloy composite improves the hardness, yield strength, and ultimate tensile strength by 1.4%, 9.2% and 4.0%, respectively. Some agglomeration of MWCNT was also detected in the 1.0 wt% MWCNT-A356 alloy composite. Evidences of bridging and pull-out structures of MWCNT were clearly observed indicating good wettability and load transfer strengthening mechanism. The results prove that the additional of small weight fraction of magnesium into the alloy matrix has positive impact to the mechanical strength of the composite.